Blood pressure percentiles in 22,051 German children and adolescents: the PEP Family Heart Study - Schwandt, Peter; Bertsch, Thomas (American journal of hypertension, 2015)
Background: Strong associations between blood pressure (BP) and overweight raise the question whether overweight children (body mass index (BMI) ≥85th percentile) should be included in the normative database. Methods: Using the LMS (Lamda-Mu-Sigma) method, we developed age-, gender-, and height-adjusted percentile curves for systolic blood pressure (SBP) and diastolic blood pressure (DBP) at the 50th, 85th, 90th, 95th, and 97th percentiles in 22,051 German youths (18,917 normal-weight, 1,938 overweight, and 1,196 obese) aged 3-18 years from yearly cross-sectional surveys of the PEP Family Heart Study Nuremberg. Results: Among children, we found no gender differences for BP and BMI. Male adolescents are taller and heavier. The mean prevalence of hypertension and obesity is 7.3% and 5.2% among children and 7.2% and 5.8% among adolescents, respectively. The prevalence of elevated BP increased substantially by weight groups achieving 24.4% in obese females and 21.9% in obese males with odds ratios of 5.9 (95% confidence interval (CI): 5.1-7.5) and 4.3 (95% CI: 3.5-5.2), respectively. The shapes of the 10 LMS-smoothed SBP and DBP percentile curves differ substantially between gender and weight group. The normal-weight percentiles are nearly identical with the overall growth charts, but separate percentiles for overweight and obese youths provide considerably higher values, such as 148/91 vs. 136/86 mm Hg for a 17-year-old male and 136/91 vs. 123/81 mm Hg for female, respectively, at the 90th percentile. Conclusions: Because of substantially higher BP percentiles, separate databases for overweight and obese children and adolescents are strongly recommended.
Gesehen am 11.12.2018
Online publication November 19, 2014